2019
DOI: 10.3390/f10070549
|View full text |Cite
|
Sign up to set email alerts
|

Early Tree Growth in Reclaimed Mine Soils in Appalachia USA

Abstract: Surface mining disturbs hundreds of hectares of land every year in many areas of the world, thereby altering valuable, ecologically-diverse forests. Reforestation of these areas after mining helps to restore ecosystem functions and land value. In Appalachia, native topsoil is normally replaced on the surface during reclamation, but waivers allow for brown and gray sandstone materials to be used as topsoil substitutes. Numerous studies report the growth of trees in these substitute mine soil materials, but few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Soil microbial community diversity is sensitive to changes in the soil physicochemical properties (Brockett et al, 2012;Dallaire and Skousen, 2019); in particular, the soil nutrients, moisture, and pH have the most obvious effects on the soil microbial community structure, which is consistent with the research results of many scholars. Zhao and Gong found that a significant correlation between soil physicochemical properties such as SOM, AK, and pH and the microbial community (Zhao et al, 2020;Gong et al, 2019).…”
Section: Response Of Soil Microbial Community To Soil Physicochemical...supporting
confidence: 87%
“…Soil microbial community diversity is sensitive to changes in the soil physicochemical properties (Brockett et al, 2012;Dallaire and Skousen, 2019); in particular, the soil nutrients, moisture, and pH have the most obvious effects on the soil microbial community structure, which is consistent with the research results of many scholars. Zhao and Gong found that a significant correlation between soil physicochemical properties such as SOM, AK, and pH and the microbial community (Zhao et al, 2020;Gong et al, 2019).…”
Section: Response Of Soil Microbial Community To Soil Physicochemical...supporting
confidence: 87%
“…A study was conducted to answer the question "Do native trees planted in mine soils grow at rates equal to or better than trees planted in native forest soils? ", where it was found tree heights for tree species in mine soils after 9 and 11 years were lower than heights estimated from pre-mining native forest soils (Dallaire and Skousen, 2019).…”
Section: Introductionmentioning
confidence: 76%
“…On the other hand, S. robusta in the natural forest stored 117.63 Mg•C•ha −1 which is greater than the afforested site. A study of early tree growth at the reclaimed coal mine site in Appalachia, USA, reported a 50% lower growth compared to the native forest [22]. Growth of the afforested tree species along the afforestation age increases the potential for carbon storage in phytomass.…”
Section: Carbon Storage In Plant and Soilmentioning
confidence: 99%
“…The introduction of leguminous trees and grass-legume association enhances the nutrient content, and their litter below and above the soil enhances the microbial activity and rapid soil formation resulting in elevated carbon sequestration in multiple mine sites [20,21]. A multi-purpose tree plantation on former mine land also increases soil quality and ecosystem carbon pool along with the age of revegetation [22][23][24][25]. We hypothesized that the introduction of fast-growing trees with an appropriate mix can accelerate the recovery of mine-degraded land and increase carbon storage in the post-mining ecosystem.…”
Section: Introductionmentioning
confidence: 99%